Evaluation of benzenesulfonyl hydrazide concentration on mechanical properties, swelling and thermal conductivity of thermal insulation from natural rubber - Padakan, Rungtawee; Radagan, Surachai (Agriculture and Natural Resources, 2016)
Abstract An experiment was carried out to obtain the optimum natural rubber thermal insulation for a refrigeration and air conditioning system. Thermal insulation not only adds value to the rubber, but also develops an improved new product from natural rubber. Concentrations of benzenesulfonyl hydrazide (BSH) blowing agent at 2, 4, 6, 8 and 10 parts per hundred of rubber (phr) were used to study the effect of the BSH concentration on the mechanical properties, swelling and thermal conductivity of thermal insulation which were evaluated using the American Society for Testing and Materials (ASTM) standards (ASTM D412, ASTM D471 and ASTM C518, respectively). The rubber compound was prepared using a two-roll mill and expanding in a hot mould at 150 oC. The results showed that both the average values of the tensile modulus and tensile strength were reduced by 25%. The average value of elongation at break not only increased by 33% before thermal aging, but also reduced by 33% after thermal aging. The maximum value of swelling was 324%. Moreover, the lowest value of thermal conductivity was 0.040 W/ m/K. Therefore, the optimum concentration of the BSH was 6 phr which had optimum properties for thermal insulation.